Effects of spirulina (Arthrospira platensis) as feed additive of steers consuming high energy diets: growth performance and nutrient digestion - Plascencia, Alejandro; Martínez-Alvarez, Iván Guadalupe; Montano, Martín; Estrada-Angulo, Alfredo; Urías-Estrada, Jesús David; Castro-Pérez, Beatriz Isabel; Zinn, Richard Avery (Journal of the Hellenic Veterinary Medical Society, 2022)
Two trials were performed in order to evaluate the effects of spirulina platensis (SP) supplemented (0, 0.5, and 1.0% of diet DM) in high-energy diet on nutrient digestion and growth-performance of feedlot cattle. The dose of each treatment was top dressed and mixed directly with the basal diet at time of feeding. In Trial 1, six cannulated Holstein steers (281±2 kg) were used in a replicated 3×3 Latin square experiment. Supplemental SP did not affect ruminal and total tract nutrient digestion. Ruminal microbial efficiency (quadratic component, P=0.06), nitrogen efficiency (linear component, P=0.10) and ruminal pH (linear, P=0.06) tended decrease with SP supplementation, without effects on ruminal VFA or estimated methane production. In Trial 2, 108 medium-frame crossbred steers (182±1 kg) were used in a 211-d study to evaluate growth performance. Supplemental SP did not affect feed intake, but linearly tended (P=0.09) to decrease weight gain, gain efficiency, and estimated dietary net energy. Supplemental SP tended (P=0.08) to linearly increase steer morbidity. Effects of SP supplementation on carcass characteristics was non-appreciable, but tended (P=0.06) linearly decrease longissimus muscle area. It is concluded that low level spirulina supplementation (up to 1% of diet) did not appreciably affect nutrient digestion, ruminal fermentation, growth-performance or health of feedlot cattle fed a high-energy diet.